2015
DOI: 10.1111/bcpt.12374
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DMBA‐induced Oral Squamous Cells Carcinoma Growth by Brazilian Red Propolis in Rodent Model

Abstract: Abstract:We investigated the effect of oral administration of hydroalcoholic extract of Brazilian red propolis (HERP) on DMBA-induced oral squamous cell carcinomas (OSCC) in rodents. The chemical components of the HERP were assessed by high-performance liquid chromatography (HPLC). Carcinogenesis was topically induced in the lower lip of 25 rats using 9,10-dimethyl-1,2-benzanthracene (DMBA); the tumour was treated with saline (TUM1) and Tween 80 (TUM2) as well as HERP at 10, 50 and 100 mg/kg (HERP10, HERP50 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
(64 reference statements)
0
20
1
Order By: Relevance
“…Ribeiro et al . () verified that an oral administration of hydroalcoholic extract of Brazilian red propolis exerted chemopreventive effects on 9,10‐dimethyl‐1,2‐benzanthracene‐induced oral squamous cell carcinomas in rodents.…”
Section: Biological Propertiesmentioning
confidence: 72%
“…Ribeiro et al . () verified that an oral administration of hydroalcoholic extract of Brazilian red propolis exerted chemopreventive effects on 9,10‐dimethyl‐1,2‐benzanthracene‐induced oral squamous cell carcinomas in rodents.…”
Section: Biological Propertiesmentioning
confidence: 72%
“…Finally, they suggested that HERP exerts chemopreventive activity on the progression of DMBAinduced epithelial dysplasia to OSCC in an experimental model of labial carcinogenesis [23]. The study limitations included difficulty in working with animals when injected propolis and possible death rats during this study.…”
Section: Discussionmentioning
confidence: 96%
“…(Fabaceae, [ 10 ]) shows various pharmacological properties of clinical interest, also being considered a functional food [ 11 , 12 , 13 ]. In particular, and due to its significant antioxidant activity [ 14 , 15 , 16 ], Brazilian red propolis has been proposed for dermal healing [ 17 , 18 ], and for the treatment of cancer cells [ 14 , 15 , 19 , 20 ], as an antimicrobial [ 16 ], antiproliferative [ 21 , 22 ], antihypertensive [ 23 ], and as a neuroprotective [ 11 ]. Several compounds have been identified in this resin, including the isoflavonoids formononetin, biochanin A, medicarpin, and pinocembrin [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%